Examining Audit Strategies Affecting the Quality of Financial Reporting - Azizi Barani, Sajjad; Rezaei, Nader; Abdi, Rasoul; Pakmaram, Asgar (Business, Marketing, and Finance Open, 2026)
In today’s complex and dynamic world, financial reporting serves as a vital instrument for transparency and accountability in the domains of economics and business, playing an undeniable role. Auditors, by adopting various strategies such as aggressive, conservative, satisfactory, and defensive approaches, can employ different orientations in their auditing processes. The purpose of the present study is to provide an optimal model of audit strategies and examine their effect on the quality of financial reporting. This research is applied in terms of purpose and descriptive-survey in nature, conducted through both quantitative and qualitative methods. The statistical population of the study consists of all auditors who are members of the Iranian Association of Certified Public Accountants. In the qualitative phase, 10 individuals were selected for interviews to identify the components of audit strategy using the theoretical saturation method. In the quantitative phase, a sample size of 373 participants was determined from the statistical population. Data collection tools included interviews for the qualitative section and standard as well as researcher-developed questionnaires for the quantitative section. To analyze the data, content analysis was used in the qualitative phase, and structural equation modeling along with SPSS and SmartPLS software were used in the quantitative phase. The qualitative results indicate the identification of 32 components related to audit strategies. Furthermore, the quantitative findings show that all four audit strategies have a positive and significant effect on the quality of financial reporting.